Appendix 2.4: Yuchengco v. Sandiganbayan, G.R. No. 149802 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
This case—which the Marcoses categorically lost—details a scheme by which the Marcoses set up a foundation through which they held stocks of PLDT. As of this writing, the shares of PLDT reconveyed to the republic via this case are still owned by the republic; efforts to sell to private entities have thus far failed.